2006
DOI: 10.1159/000088193
|View full text |Cite
|
Sign up to set email alerts
|

Early Increased Levels of Matrix Metalloproteinase-9 in Neonates Recovering from Respiratory Distress Syndrome

Abstract: Aim: Matrix metalloproteinases (MMPs) play an eminent role in airway injury and remodelling. We explored the hypothesis that pulmonary MMP levels would differ early after birth (2–4 days) between infants with resolving respiratory distress syndrome (RDS) and infants developing chronic lung disease of prematurity (CLD). Methods: Thirty-two prematurely born infants (gestational age ≤30 weeks) diagnosed with RDS were included. In 13 infants RDS resolved while 19 developed CLD. MMP-2 and MMP-9 in bronchoalveolar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Increased production of MMP-9 from infiltrating immune cells or from the respiratory epithelium occurs in inflammatory lung diseases, and abnormal expression and activation of MMP-9 tend to accompany tissue injury and airway remodeling (Okamoto et al, 2002;Dik et al, 2005). Cataldo et al showed that deletion of the MMP-9 gene reduces peribronchial inflammation, airway lymphocyte accumulation, airway IL-13 production and the development of bronchial hyperresponsiveness (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Increased production of MMP-9 from infiltrating immune cells or from the respiratory epithelium occurs in inflammatory lung diseases, and abnormal expression and activation of MMP-9 tend to accompany tissue injury and airway remodeling (Okamoto et al, 2002;Dik et al, 2005). Cataldo et al showed that deletion of the MMP-9 gene reduces peribronchial inflammation, airway lymphocyte accumulation, airway IL-13 production and the development of bronchial hyperresponsiveness (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, for severely premature neonates, BPD/CLD shows progression towards impairment of alveolar septation from enhanced proteolysis of extracellular matrix components (30,77), coinciding with increased appearance of a number of enzymes such as neutrophil elastase and matrix metalloproteinase (MMP)-8 (20,77,79). Recent data suggest that disruption of angiogeneis (36) prevents alveolarization and development of other distal lung air space architecture (81,82), which is a major hallmark of BPD.…”
mentioning
confidence: 99%
“…The NGAL functions mainly depend on its binding activity, directed against various molecules, such as N-formylated tripeptides, fatty acids, leukotriene B4 and platelet activating factor (3) as well as plasma matrix metallo-protein MMP-9 (4). In particular, when bound to MMP-9, NGAL may modulate various inflammatory mechanisms, including acute phase proteins and the vascular repair process (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In fact, indometacin, a drug used in cases ofnewborn PDA, has been reported to decrease MMP-9 synthesis and release (10)(11) and also to reduce IL-l-beta (6)(7)(8) up-regulation of NGAL, although in a different field and in a rat model (7,12). Dexamethasone or retinoic acid treatment are able to increase NGAL synthesis as well as oxygenation (13), vascular injury and oxidative stress (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation